Case report: A combined immunotherapy strategy as a promising therapy for MSI-H colorectal carcinomas with multiple HPD risk factors - Zhang, Jinli; Yang, Lu; Kong, Fanwei; Wu, Di; Hu, Baoru; Yang, Jie; He, Jiaxin; Liu, Lei (Frontiers in Medicine, 2023)
Approximately 5% of advanced colorectal carcinomas (CRCs) and 12–15% of early CRCs are microsatellite instability-high (MSI-H) or mismatch repair-deficient (dMMR) tumors. Nowadays, PD-L1 inhibitors or combined CTLA4 inhibitors are the major strategies for advanced or metastatic MSI-H colorectal cancer, but some people still show drug resistance or progression. Combined immunotherapy has been shown to expand the benefit population in non-small-cell lung carcinoma (NSCLC), hepatocellular carcinoma (HCC), and other tumors while reducing the incidence of hyper-progression disease (HPD). Nevertheless, advanced CRC with MSI-H remains rare. In this article, we describe a case of an elder patient with MSI-H advanced CRC carrying MDM4 amplification and DNMT3A co-mutation who responded to sintilimab plus bevacizumab and chemotherapy as the first-line treatment without obvious immune-related toxicity. Our case provides a new treatment option for MSI-H CRC with multiple risk factors of HPD and highlights the importance of predictive biomarkers in personalized immunotherapy.